From Margin to Mainstream: Changes in Early Modern Netherlandish Scholarship - Kooi, Christine (The sixteenth century journal, 2019)
The author discusses the changes in scholarship of the Renaissance in the Low Countries. She mentions the benefits of working in the well-organized Dutch and Belgian archives, the internationalization of research in Low Country Renaissance, and the inclusion of the Catholic experience.